Efisiensi Pengolahan Cr(VI) dengan Resin Immobilized Photocatalyst Technology (RIPT) Katalis ZnO - Zahrah, Aurelia Asilah; Purnomo, Yayok Suryo; Murti, Restu Hikmah Ayu (Jurnal Serambi Engineering, 2025)
Waste water from the nickel mining process has the potential to contaminate the environment due to the presence of hazardous metals such as chromium (Cr) in the form of Cr(VI) and Cr(III), iron (Fe), nickel (Ni) and other heavy metals. These substances are of great concern because of their toxicity, which can have adverse effects on ecosystems and human health. This study was conducted to investigate the effects of UV-C lamp light intensity, contact time and RIPT-ZnO weight on the removal of hexavalent chromium (Cr(VI)) from nickel wastewater. The method used in this research involved immobilisation of photocatalysts on resin with RIPT concentrations of 5g, 10g and 15g and variations in UV-C lamp light intensity of 8W, 18W and direct sunlight. The contact times tested were 0 minutes, 30 minutes, 60 minutes, 120 minutes and 180 minutes, with the focus of the analysis on the Cr(VI) concentration. The results showed that increasing RIPT dosage resulted in higher Cr(VI) removal percentages. The highest Cr(VI) removal was achieved with a 15 gram RIPT dosage, especially when ZnO was used. The optimum contact time for maximum Cr(VI) removal was 180 minutes, indicating that the longer the wastewater is exposed to RIPT, the higher the removal rate. The study found that the use of ZnO in the RIPT technology achieved the highest Cr(VI) removal efficiency, reaching 96%.